Smart Learning Companion (SLAC) - Bibi, Syeda Hamna; Munaf, Rumsha Muhammad; Bawany, Narmeen Zakaria; Shamim, Arifa; Saleem, Zara (International Journal of Emerging Technologies in Learning (iJET), 2020)
Augmented Reality (AR) tends to merge the computing world with the real world, giving way to an incredible user experience. This field is not only limited to entertainment but has been utilized in various domains including healthcare, education and training. Realizing the potential of Augmented Reality in improving the learning experience, researchers have explored many ways of incorporating AR in the field education. Consequently, this research is focused on providing interactive and customized learning experience to book readers. We present a mobile application, Smart Learning Companion (SLAC), for physical books that provide a virtual content for a book. The virtual content include, 3D animations, Quizzes, explanation of content in native language and many other features. The virtual content is activated as soon as pages are scanned with a mobile phone or tablet. Smart Learning Companion explains animated educational content and provides an interactive user experience. The aim of SLAC is to encourage students to learn on their own by making books more interactive. Smart Learning Companion provides explanation in Urdu, solutions of exercises with animations, quizzes for each section, and overall result that shows the student progress. This will help to reduce the dependency of students on others for learning making them capable of self-learning. Smart Learning Companion applications are developed for four books to conduct the experiments. Experimental study is conducted to show the effectiveness of Smart Learning Companion application. The results show that our application helped students to understand the concepts more easily as explanation was provided in national language of Pakistan, that is, Urdu.